Study of biological synthesized silver nanoparticles of aqueous extract of Imperata cylindrica against bacterial contaminants from domestic waste water - Mani, Vicky; Ramaswamy, Uma (Journal of Environmental Engineering and Landscape Management, 2021)
The present study focus on the green synthesis and characterization of Imperata cylindrica silver nanoparticle and its efficiency against isolated bacterial contaminants from domestic waste water. 5% aqueous Imperata cylindrica extract (AEIC) was treated with 1 mM concentration of Silver Nitrate at 37 °C for silver nanoparticle synthesis. Domestic waste water treated with AEIC and AgNP’s of IC with different time durations (12, 24 and 48 hrs). Selective agar media’s is used for isolation of specific bacterial species. Surface Plasmon resonance occurred at 430 nm for 1 mM silver nitrate and AgNP’s are spherical and size ranges from 70–80 nm. As the incubation time proceeds after 12, 24 and 48 hours the number of colonies decreased in AEIC and AgNP treated samples. These results showed that AgNP’s of I.cylindrica treated sample has the good ability to inhibit E.coli, Salmonella, Phosphate solubilizing bacteria and Shigella in domestic sewage water when compared to AEIC in 48 hours.